The influence of parents divorce on the child personality development in nicholas sparks' the last song novel (2009): a developmental psychology approach - Ningrum, Eny Setia; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
This study is about the influence of parents divorce on the child personality development of the major character in The Last Song novel. The problem of this study is how parents divorce influence on the child personality development reflected at Nicholas Sparks' The Last Song Novel (2009) viewed from developmental psychology approach. The objectives of this study are identify the structural elements and the developmental psychology approach in The Last Song novel. The object of the study is Nicholas Sparks'The Last Song novel (2009). It is analyzed by using a developmental psychologyapproach. This study is qualitative research. There are two sources that are needed to do this research, namely: primary data sources and secondary data sources. The primary da ta sources are Nicholas Sparks'The Last Song novel (2009). The secondary data sources from other sources related the study, such as: website, dictionary, some book that support the analysis. The result of the study shows the following conclusions.Firstly, based on the structural analysis, it can be concluded that in this novel, the author communicates his message to the reader that the parents divorce influences on the child personality development. Secondly, based on the developmental psychology approach, it can be concluded that in this novel, the author creates Ronnie as major character to illustrate a psychological phenomenon as a personality who changed her behavior because of her parents divorce.